Pharmaceutical Hydrogels: A Comprehensive Review - Pradeep H K; Dipti H Patel; Laxmi M; Pratiksha C C; Girish Bolakatti; Praveen Kumar G M; Abhay Sapre; Madhu kumar H M (Rajiv Gandhi University of Health Sciences, 2024)
Three-dimensional hydrophilic polymeric networks called hydrogels can absorb vast volumes of fluids present in the body or water. Among synthesized biomaterials they most nearly resemble natural living tissues because of their high-water content porosity and soft consistency. To customize hydrogels for particular purposes cellulose functionalization offers improved physical and chemical properties as well as control over biological interactions. Here we provide a critical evaluation of hydrogels utilized in biomedicine. Hydrogels encourage cell regeneration while providing the necessary mechanical qualities for tissue engineering scaffolds advantageous in treating wounds and repairing cartilage. Hydrogels have become a highly customizable platform for a variety of biomedical applications offering effective and sustainable solutions for the life sciences. In this review article an attempt was made to discuss the processes for developing hydrogels prepared from hydrophilic polymers of synthetic and natural origin with a focus on naturally occurring biopolymers that are water-soluble hydrocolloids and their proposed applications were also reviewed.